2019
DOI: 10.1002/ange.201902380
|View full text |Cite
|
Sign up to set email alerts
|

Formiat‐Oxidase (FOx) aus Aspergillus oryzae: ein Katalysator für verschiedene H2O2‐abhängige biokatalytische Oxidationen

Abstract: Ein Vielzahl biokatalytischer Oxidationsreaktionen verwendet H 2 O 2 als Oxidationsmittel. Oftmals erfordert allerdings die geringe Stabilitätv on Enzymen die Verwendung eines effizienten In-situ-H 2 O 2 -Generierungssystems.I nA nlehnung an die fürN ADH-abhängige Reaktionen weit verbreitete Formiat-Dehydrogenase schlagen wir hier die Verwendung einer Formiat-Oxidase (FOx) vor,u mH 2 O 2 -abhängige enzymatische Oxidationen anzutreiben. Bereits unter nicht-optimierten Bedingungen wurden sehr vielversprechende K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Oxidase‐based H 2 O 2 ‐generation systems have therefore attracted a great deal of attention because they are user‐friendly, cost‐effective and sustainable (Scheme 2). Among these, the implementation of formate oxidase (FOx, EC 1.2.3.1) is especially interesting since it only produces CO 2 as a by‐product, [7] but a more robust FOx with a lower K m is desired [7a] . Inspired by the studies on FOx, we show here for the first time that oxalate oxidase (OXO, EC 1.2.3.4) [8] is an efficient alternative as an H 2 O 2 ‐source for the C−H oxyfunctionalisation reactions catalysed by UPOs.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidase‐based H 2 O 2 ‐generation systems have therefore attracted a great deal of attention because they are user‐friendly, cost‐effective and sustainable (Scheme 2). Among these, the implementation of formate oxidase (FOx, EC 1.2.3.1) is especially interesting since it only produces CO 2 as a by‐product, [7] but a more robust FOx with a lower K m is desired [7a] . Inspired by the studies on FOx, we show here for the first time that oxalate oxidase (OXO, EC 1.2.3.4) [8] is an efficient alternative as an H 2 O 2 ‐source for the C−H oxyfunctionalisation reactions catalysed by UPOs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that the formate oxidase from Aspergillus oryzae ( Ao FOx) is an efficient catalyst for the in situ generation of H 2 O 2 to drive peroxygenase‐catalysed oxyfunctionalisation reactions . Encouraged by the very promising results, we originally aimed at a further characterisation of Ao FOx.…”
Section: Figurementioning
confidence: 99%
“…Recombinant expression and purification of the evolved unspecific peroxygenase mutant from A. aegerita in P. pastoris was performed following a previously described procedure . Formate oxidase from Aspergillus oryzae RIB40 ( Ao FOx) was produced recombinantly in E. coli BL21(DE3) as reported before with slight modifications . During desalting step with HiTrap, an additional buffer exchange was applied by using a phosphate potassium buffer (25 mM, pH 6.0) for elution of the target enzyme of the column.…”
Section: Figurementioning
confidence: 99%
“…As such numerous systems have been developed to supply in‐situ synthesised H 2 O 2 to UPOs, these include the use of enzymatic cascades, with the use of glucose oxidase (GO X ), formate oxidase (FOx) or choline oxidase (ChOx) co‐enzymes previously reported [8–11] . However, such approaches so far have been hampered by poor atom efficiency and the formation of undesirable by‐products [12] …”
Section: Introductionmentioning
confidence: 99%